Coefficient inverse problem for the strongly degenerate parabolic equation - Huzyk, N.M.; Pukach, P.Y.; Vovk, M.I. (Carpathian Mathematical Publications, 2023)
The coefficient inverse problem for the degenerate parabolic equation is investigated. The minor coefficient of this equation is the polynomial of the first power with respect to the space variable with two unknown time-dependent functions. The investigation is carried out under given inhomogeneous initial condition, Dirichlet boundary conditions and integral overdetermination conditions. We establish the conditions of the unique solvability to the named problem for the case of strong degeneration.